ANALISIS STRATEGI PENINGKATAN PRODUKSI KOMODITI KAKAO RAKYAT DI KECAMATAN SILAU LAUT (Studi Kasus : Desa Lubuk Palas Kecamatan Silau Laut Kabupaten Asahan Provinsi Sumatera Utara) - Roma Uli Esteria Lumban Toruan; Diana Chalil; Kelin Tarigan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Sumatera Utara, 2017)
ABSTRACT Cacao is a plantation crop which plays a quite important role in national economy. It reaches its peak production at the age of 10 to 20 years with maximum production per hectare reaches 3,700 kg/ha/year. The increase in the number of cacao land areas and its annual production are taken into government’s consideration to increase income. Cacao is the annual crop that is not easily replaced like seasonal crops when loss is incurred. The strategy to increase cacao production well is required through studying the internal and external factors which should be done empirically to analyze obstacles, opportunities, probabilities and threats in Asahan Regency. The samples were the Plantation and Forestry Agency of Asahan Regency, cacao collectors, and cacao farmers at Lubuk Palas Village, Asahan Regency. The strategies obtained in this research are: 1) Introducing the practices, innovations, and latest technology through trainings in accordance with the farmers’ experience in cacao farm; 2) Making intensive coordination with the institutions, merchants, and farmers to maintain the stability of cacao price; 3) Increasing the security, cultivation, and monitoring of the evaluation of production facility assistance as the institution that makes subsidy distribution program to the procurement of top-quality seeds in the field; 4) Implementing the appropriate technology package that can be adopted by the farmers through equipment procurement assistance to improve the land quality; and 5) Making intensive use of capital assistance to establish modern cacao farmers. Keywords: Cacao, SWOT Strategy for Production Increase, Internal and External Factors.